Contemporary view to the history of Kazakhstan's democratic journalism and publicism - Sailaukyzy, Alma; Shakuova, Rima; Sak, Kairat; Lebedeva, Tatiana (Opción, 2019)
In this article, the types of publicism of Alash party members and quality of their work from democracy discourse is analyzed. Alash intellectuals could resist to colonial policy of the Empire by using publicism as the fight tool against this policy. Basing on written works by Alash publicists and journalists, we can see an excellent example of influencing the public insight by generating public opinion. Scientists and young people from Kazakhstan who have a considerable place in today's Central Asia are reflected in the questionnaire on what they think on journalism history and its role as a national brand.